Acceptability of the Cognition Test Battery in astronaut and astronaut-surrogate populations - Casario, K.; Howard, K.; Cordoza, M.; Hermosillo, E.; Ibrahim, L.; Larson, O.; Nasrini, J.; Basner, M. (Acta astronautica, 2022)
Sustained high levels of astronaut cognitive performance are a prerequisite for mission success. A neuropsychological battery of 10 brief cognitive tests (Cognition) covering a range of cognitive domains was specifically developed for high performing astronauts to objectively assess cognitive performance. Extended mission durations require repeated cognitive testing and thus high acceptability of the Cognition software to the astronaut population. The aim of this qualitative study was to evaluate acceptability of Cognition to astronauts and astronaut surrogate populations. Cognition was administered repeatedly to N = 87 subjects (mean age ± SD 35.1 ± 8.7 years, 52.8% male) on a laptop or iPad across five individual studies on the International Space Station or in space analog environments on Earth. Following completion of each study, participants were interviewed regarding their experience using Cognition in a semi-structured debrief. Participant comments were analyzed using a qualitative conventional content analysis approach. The majority of participants’ comments (86.1%) were coded as positive or neutral in valence, with most positive comments relating to software usability, engagement, and overall design. Among the 10 Cognition tests, subjects liked the Visual Object Learning Test most (28 likes, 32.2% of participants), while the Emotion Recognition Test was liked least (44 dislikes, 50.6% of participants). Some subjects (36.8%) were frustrated with the level of difficulty of some of the 10 Cognition tests, especially during early administrations, which was by design to avoid ceiling effects in repeated administrations of high-performers. Technical difficulties were rare (20.7% of participants), and most often observed in environments with restricted internet access. Most participants (82.3% of those who commented) liked the feedback provided by Cognition after each test, which includes a graph showing performance history. Cognition was found to be acceptable to astronaut and astronaut-surrogate populations across a variety of settings and mission durations. Participant feedback provided was used to further improve Cognition and increase its acceptability during sustained space missions. •Cognition was specifically designed for monitoring high-performing astronauts on long-duration space missions.•A qualitative conventional content analysis of debriefs demonstrates that Cognition is acceptable the relevant population.•The feedback provided by study participants was used to further improve Cognition validity and acceptability.